2015
DOI: 10.17957/ijab.17.3.14.257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Embryo-like Structure and Callus Formation in Unpollinated Ovary Culture of Cucumber (Cucumis sativus)

Abstract: To cite this paper: Tantasawat, P.A., A. Sorntip, O. Poolsawat, W. Chaowiset and P. Pornbungkerd, 2015. Evaluation of factors affecting embryo-like structure and callus formation in unpollinated ovary culture of cucumber (Cucumis sativus AbstractThe effects of various factors including genotypes of donor plants, induction and differentiation media, and thermal shock pretreatment were evaluated on embryo-like structure (ELS) and callus formation in an unpollinated ovary culture of cucumber. All five cucumber c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
2
13
0
2
Order By: Relevance
“…Previously, we evaluated factors influencing the induction of ELSs and calli in unpollinated ovary culture of five Thai cucumber cultivars and found that donor plant genotypes and induction media, differing in PGRs, affected both ELS and callus formation. The addition of TDZ and 6-benzylaminopurine (BAP) into the induction medium resulted in the highest percentage of ELS formation (Tantasawat et al, 2015). Similarly, the addition of TDZ increased embryogenesis success in ovary/ovule culture in other studies (Li et al, 2013;Moqbeli et al, 2013;Suprunova and Shmykova, 2008).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Previously, we evaluated factors influencing the induction of ELSs and calli in unpollinated ovary culture of five Thai cucumber cultivars and found that donor plant genotypes and induction media, differing in PGRs, affected both ELS and callus formation. The addition of TDZ and 6-benzylaminopurine (BAP) into the induction medium resulted in the highest percentage of ELS formation (Tantasawat et al, 2015). Similarly, the addition of TDZ increased embryogenesis success in ovary/ovule culture in other studies (Li et al, 2013;Moqbeli et al, 2013;Suprunova and Shmykova, 2008).…”
mentioning
confidence: 83%
“…Unpollinated ovary culture. Pistillate flowers, 12 h before anthesis, were obtained from donor cucumber plants, and unpollinated ovaries were sterilized according to Tantasawat et al (2015). Longitudinal sliced ovaries were placed on three different induction media.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these difficulties, to inducing gynogenesis in vitro, especially when the haploid induced by the male gametophyte is not successful or the induction rate is too low and when self-incompatibility, male-sterile and dioecious plants occurs, is an effective way to obtain haploid or double haploid plants [3]. In vitro gynogenesis is mainly used in the Cucurbitaceae, and previous studies have revealed that this technique is still imperfect and that the embryogenesis rate is low [4][5][6][7][8][9][10][11]. The study of the mechanism of embryogenesis has therefore been delayed, and the understanding of the mechanisms underlying gynogenesis induction is extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…Diao et al, 2009;Moqbeli et al, 2013;Tantasawat et al, 2015;Sorntip et al, 2017) Suprunova, Shmykova (2008). использовали в своих исследованиях среду МСм (Masuda et al, 1981).…”
unclassified